Assessment of factors affecting Filipino consumers’ purchasing intent towards processed meat during COVID-19 - Ang, Aaron Shaun A. (College of Home Economics, University of the Philippines, 2023)
Amidst the various changes caused by the COVID-19 pandemic towards peoples’ lifestyles, particularly the manner in which food is purchased and consumed, there is much to know regarding such patterns and how this may affect the likelihood of purchasing processed meat. Utilizing a Theory of Planned Behavior-based approach, this research assessed the underlying factors surrounding pandemic-induced food-related lifestyle changes, and illustrated the relation of research constructs with purchasing intent for processed meat. Data was designed to be collected via online platforms, spamming two phases employing both factor analysis (n = 150) and structural equation modeling (n = 300). Sustainable Food choices, consumer attitudes, subjective norms, and to a certain extent, changes in food shopping patterns, were shown to have manifested the most impacts towards purchasing intent for processed meat at 5% significance despite rather mediocre path coefficient values.